Plate corner subduction and rapid localized exhumation: Insights from 3D coupled geodynamic and geomorphological modelling. (25th February 2022) - Koptev, Alexander; Nettesheim, Matthias; Ehlers, Todd A.
Abstract: Rapid, localized exhumation has been reported at many plate corners between adjacent subduction/collision segments. Here we use a fully‐coupled geodynamic and geomorphological modelling approach to investigate overriding plate deformation and resulting rock uplift patterns in these narrow, cuspate regions. In this study, we focus on the effects of internal deformation within a subducting convex‐upward‐shaped indenter and the strength of the interface between the upper and downgoing plate. The strongest localization of high rock uplift rates in the region above the indenter apex is predicted in experiments with a deformable lower plate, a weak interface layer and lateral shortening accommodated only by subduction (i.e., without an upper plate advance component). Our results suggest that bull's eye shaped structures characterized by young thermochronological ages can, in principle, be reproduced numerically when taking into account a non‐rigid subducting plate together with complex brittle‐ductile rheology and stratification of the overriding lithosphere and realistically implemented fluvial erosion at its surface.